PENGARUH INFORMASI KESEHATAN TERHADAP PENGETAHUAN REMAJA TENTANG BAHAYA MEROKOK DI MAN 1 POHUWATO - Lenny Ali; Harismayanti Harismayanti (program studi ilmu keperawatan fakultas ilmu kesehatan universitas muhammadiyah gorontalo, 2021)
Smoking is one problem that is difficult to solve. So that smoking should be treated as an effort as early as possible by providing health information. The purpose of this study was to determine the effect of giving health information on adolescent knowledge about the dangers of smoking. The design of this study uses quasy experiments pre-test post with the design of the Two Group pre-test post. The population in this study is amounted to 87 students and a sample of 32 respondents with random sampling and data analysis using paired t-test. The results showed that the experimental group was 0.001 (p <0.05) and the control group was 0.164 (p <0.05). In conclusion, there is influence of health information on adolescent knowledge in MAN 1 Pohuwato.